Secukinumab shows high efficacy irrespective of HLA‐Cw6 status in patients with moderate‐to‐severe plaque‐type psoriasis: SUPREME study. (14th August 2018) - Costanzo, A.; Bianchi, L.; Flori, M.L.; Malara, G.; Stingeni, L.; Bartezaghi, M.; Carraro, L.; Castellino, G.; ,
Summary: Background: Understanding genetic variations is important in predicting treatment response and forms the basis for identifying new pharmacogenetic and pharmacogenomic targets for psoriasis treatment. There are limited data on the efficacy of secukinumab in relation to genetic markers. Objectives: To evaluate the efficacy and safety of secukinumab 300 mg in HLA‐Cw6 ‐positive (Cw6‐POS) and HLA‐Cw6 ‐negative (Cw6‐NEG) patients with moderate‐to‐severe chronic plaque‐type psoriasis. Methods: SUPREME was a 24‐week, phase IIIb study with an extension period up to 72 weeks. Primary end point was Psoriasis Area Severity Index (PASI) 90 response rate after 16 weeks. Results: In total, 434 patients were recruited: 185 (42·6%) were Cw6‐POS and 246 (56·7%) were Cw6‐NEG (three not assessed). Mean ± SD age was 45·2 ± 13·2 years (Cw6‐POS 42·7 ± 13·1; Cw6‐NEG 47·2 ± 12·9). The baseline PASI score was comparable between the cohorts [Cw6‐POS 20·7 ± 8·99; Cw6‐NEG 21·5 ± 9·99 ( P = 0·777)]. At week 16, PASI 90 was achieved in 80·4% of Cw6‐POS and 79·7% of Cw6‐NEG patients (difference 0·76; 95% confidence interval −7·04 to 8·23). No differences in absolute PASI at week 16 (Cw6‐POS 1·36 ± 3·58; Cw6‐NEG 1·18 ± 2·29) were observed. The overall safety profile of secukinumab was consistent with that previously reported. No statistically significant difference was detected in the rate of treatment‐emergent adverse events [Cw6‐POS 42·7%; Cw6‐NEG 49·6% ( P = 0·295)]. A high PASI 90 response was achieved with secukinumab with a fast reduction in absolute PASI. Conclusions: Determination of HLA‐Cw6 status for secukinumab therapy is unnecessary, as it is highly effective regardless of HLA‐Cw6 status. Abstract : What's already known about this topic? HLA‐Cw6 is associated with the phenotypic features of psoriasis and positive response to ustekinumab and is present in approximately 40–80% of cases. Secukinumab is a fully human monoclonal antibody neutralizing interleukin‐17A and it has demonstrated a rapid onset of action and sustained responses with a favourable safety profile in moderate‐to‐severe psoriasis, psoriatic arthritis and ankylosing spondylitis. What does this study add? Although HLA‐Cw6 ‐positive and HLA‐Cw6 ‐negative patients have distinct clinical features, the present study showed that secukinumab achieved similar clinical responses in both cohorts after 24 weeks of treatment. There was no difference in efficacy regarding HLA‐Cw6 status. Respond to this article Plain language summary available online